Fanum world - Tan, Yen Ling (Nanyang Technological University, 2022)
Social media is changing the way celebrities communicate and connect with their fans, and for fans to form communities. However, an intense common identity and anonymity can also fuel toxic behaviours or even online abuse, and this can have a detrimental effect on young people involved in fandom.